Evaluation of anakinra in the management of patients with COVID-19 infection: A randomized clinical trial - Elmekaty, Eman Zeyad I.; Maklad, Aya; Abouelhassan, Rawan; Munir, Waqar; Ibrahim, Mohamed Izham Mohamed; Nair, Arun; Alibrahim, Rim; Iqbal, Fatima; Al Bishawi, Ahmad; Abdelmajid, Alaaeldin; Aboukamar, Mohamed; Hadi, Hamad Abdel; et al. (Frontiers in Microbiology, 2023)
Background: The global COVID-19 pandemic led to substantial clinical and economic outcomes with catastrophic consequences. While the majority of cases has mild to moderate disease, minority of patients progress into severe disease secondary to the stimulation of the immune response. The hyperinflammatory state contributes towards progression into multiorgan failure which necessitates suppressive therapy with variable outcomes. This study aims to explore the safety and efficacy of anakinra in COVID-19 patients with severe disease leading to cytokine release syndromes. Methods: In this open-label, multicenter, randomized clinical trial, patients with confirmed COVID-19 infection with evidence of respiratory distress and signs of cytokine release syndrome were randomized in 1:1 ratio to receive either standard of care (SOC) or anakinra (100mg subcutaneously every 12 hours for 3 days then 100mg subcutaneously once daily for 4 days) in addition to SOC. The primary outcome was treatment success at day 14 as defined by the WHO clinical progression score of ≤3. Primary analysis was based upon intention-to-treat population, with p-value of <0.05. Results: Out 327 patients screened for eligibility, 80 patients were recruited for the study. The mean age was 49.9 years (SD=11.7), with male predominance at 82.5% (n=66). The primary outcome was not statistically different (87.5% (n=35) in anakinra group vs. 92.5% (n=37) in SOC group, p=0.712; OR=1.762 (95%CI: 0.39-7.93). The majority of reported adverse events were mild in severity and not related to the study treatment. Elevated aspartate aminotransferase was the only significant adverse event which was not associated with discontinuation of therapy. Conclusion: In patients with severe COVID-19 infection, the addition of anakinra to SOC treatment was safe but was not associated with significant improvement according to the WHO clinical progression scale. Further studies are warranted to explore patients’ subgroups characteristics that might benefit from administered therapy. The study was registered in ClinicalTrials.gov, identifier: NCT04643678.